The Characteristics of Muscle Soreness – Delayed Onset Muscle Soreness in Sport Person from South Sulawesi - Nurussyariah, Nurussyariah; Setyagraha, Etno; Ichsania, Nurul; Putra, Guruh Amir (Gema Wiralodra, 2024)
Muscle Soreness – Delayed Onset Muscle Soreness (MS – DOMS) is the immediate and delayed muscle pain experienced by individuals after exercising. This study aims to observe the characteristics of MS-DOMS and the pattern of dietary intake and physical activity of athletes in South Sulawesi. The research method used was an observational description method with cross sectional design using a closed-ended questionnaire given to 211 samples categorized as athletes and non-athletes in South Sulawesi. The questionnaire was distributed using G.Forms and QR codes. The questionnaire used was a modified between the McGill Pain Questionnaire and the numerical pain scale, SQ – FFQ, as well as the form of physical activity performed. The indicators of the questions include physical activity, dietary patterns, and the characteristics of muscle pain. This study took place from May to October 2024. The results obtained showed that 69.2% of respondents experienced muscle pain after exercise, with 44.4% experiencing it less than 6 hours after exercise, with a duration of pain felt for less than 6 hours (44.2%). The most common location of muscle pain was in the thighs (31.8%) with a pain scale of 3 (19%), while the pain felt after 24 hours received the most answers, scale 3 and 5 (17.5%).